Epoxy-vitrimer composites based on exchangeable aromatic disulfide bonds: Reprocessibility, adhesive, multi-shape memory effect. (27th May 2020) - Ji, Fance; Liu, Xiangdong; Sheng, Dekun; Yang, Yuming
Abstract: Vitrimers are a class of polymers integrating the advantage of thermosets and thermoplastics. The dynamic crosslinking networks endow vitrimers with interesting rheological behavior and functional applications, such as self-healing, thermally plasticity and shape memory properties. Here, based on the dynamic aromatic disulfide bonds, a series of vitrimer composites with reconfigurability and tunable mechanical properties were successfully prepared. Using the time-temperature superposition, we prove that the relaxation of vitrimer composites should be divided into two distinct parts, including the topological rearrangement of epoxy network and the relaxation of thermoplastic components. Meanwhile, the physical entanglement of thermoplastics and the reconfigurability of chemical cross-links enable vitrimer composites to have excellent adhesive property. Based on the reconfigurability of vitrimer composites, the multi-shape memory effect was readily realized through blending the vitrimer composites of different glass transition by a simple hot-pressing method. It is anticipated that this novel strategy will pave way for the fabrication of thermosetting polymers with both reconfigurability and functional applications. Graphical abstract: Image 1 Highlights: The obtained vitrimer composites exhibit good recycling abilities. The rheological test was conducted by time−temperature superposition. A novel strategy to design multi-shape memory polymers was reported.